2013
DOI: 10.1152/ajpendo.00492.2012
|View full text |Cite
|
Sign up to set email alerts
|

Menopause is associated with decreased whole body fat oxidation during exercise

Abstract: insulin sensitivity was obtained from an oral glucose tolerance test. Body composition was measured by dual-energy X-ray absorptiometry and magnetic resonance imaging. Fat oxidation and energy expenditure were measured during an acute exercise bout of 45 min of ergometer biking at 50% of maximal oxygen consumption (V O2 max). Muscle biopsies from the vastus lateralis of the quadriceps muscle were obtained before and immediately after the exercise bout. Postmenopausal women had 33% [confidence interval (CI) 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
56
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 55 publications
12
56
1
2
Order By: Relevance
“…Many postmenopausal women gain body weight due the natural decrease in endogenous estradiol levels during menopause and reductions in energy expenditure can be prevented by estrogen replacement therapy (Gambacciani et al, 1997). Additionally, postmenopausal women have a lower fat oxidation and energy expenditure during exercise and sleep when compared to premenopausal women (Abildgarrd et al, 2013; Lovejoy et al, 2008). Rodent studies have confirmed these findings and identified that activation of the estrogen receptors in the ventral medial nucleus of the hypothalamus results in increased energy expenditure (Musatov et al, 2007; Xu et al, 2011).…”
Section: Estrogens and Adipositymentioning
confidence: 99%
“…Many postmenopausal women gain body weight due the natural decrease in endogenous estradiol levels during menopause and reductions in energy expenditure can be prevented by estrogen replacement therapy (Gambacciani et al, 1997). Additionally, postmenopausal women have a lower fat oxidation and energy expenditure during exercise and sleep when compared to premenopausal women (Abildgarrd et al, 2013; Lovejoy et al, 2008). Rodent studies have confirmed these findings and identified that activation of the estrogen receptors in the ventral medial nucleus of the hypothalamus results in increased energy expenditure (Musatov et al, 2007; Xu et al, 2011).…”
Section: Estrogens and Adipositymentioning
confidence: 99%
“…Hence, MHT may be a factor that affects auditory function. Second, the benefits of exercise for postmenopausal health or neurocognitive function are related to a number of confounding factors, such as body mass index (BMI), personal history of diabetes mellitus and cardiovascular disease and smoking status [21][22][23][24][25][26][27][28] . Third, a series of experiments demonstrated that high-intensity levels of exercise alter the RT 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased incidence of metabolic diseases during menopause is associated with changes in body composition, as postmenopausal women have decreased skeletal muscle mass [7][9] as well as increased visceral fat mass [9], [10]. Furthermore, postmenopausal women have lower whole body fat oxidation rates compared to premenopausal women [9], [10], a phenomenon known to lead to obesity [11] and dyslipidemia [12]. As a consequence of inadequate fat oxidation, excess adiposity often leads to ectopic fat storage of lipid metabolites including triacylglycerols (TAGs), diacylglycerols (DAGs) and ceramides in metabolic tissues such as skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%